Housing provision in Transit-Oriented Development (TOD) for advancing sustainable development goal - Badaruddin, Suraya; Marzukhi, Marlyana Azyyati; Shamsuddin, Siti Mazzuana; Danial, Muhammad Hakim; Hasibun, Hayati Sari; T Permana, Chrisna (UiTM Press, 2025)
Human settlement is associated with shelter for the people and their daily needs (employment, recreation including other activities) which influence their travel behaviour. Furthermore, the provision of housing near the transportation system is significant to enable people to reach their desired destinations. This paper aims to explore how housing provision In TransitOriented Development (TOD) areas contributes towards achieving sustainable development objectives by examining the relationship between TOD, housing and sustainable development. Transit- oriented development concepts and principles including the implementation of such a concept towards sustainability will be elaborated based on evidence found in related articles from the past research. Thus, the integration of key components such as transportation and land-use are the pre-requisites and must be supported by a comprehensive plan, good governance and, coordination between agencies at federal, state and, local levels towards ensuring the success of TOD objectives. However, such integration for TOD planning, especially in existing urban areas, remains a challenge. The challenges include existing urban areas with limited space to accommodate housing in the area. The study conducts qualitative research and semi-structured interview with nine (9) respondents who were selected based on their profession and position in their respective organisations. This paper will substantiate the above claims and reinforce the idea of why planning for housing in TOD areas is important in supporting sustainable development objectives.